2013
DOI: 10.1016/j.seizure.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum S-100B levels in children with temporal lobe epilepsy

Abstract: Our data suggest that increased S-100B protein levels in the serum might reflect neuronal damage in the brains of children with temporal lobe epilepsy. These results do confirm the previous findings of elevated S-100B protein levels in adult patients with temporal lobe epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…For example, high levels of S100B in the serum of the cerebrospinal fluid have been reported for schizophrenia [17,18] , major depression [19] , traumatic brain damage [20,21] , brain ischemia [22,23] , neurodegenerative disease [24,25] , and during acute episodes of bipolar disorder [26] . In addition, Calik et al [27] showed elevated S100B levels in patients with different kinds of epilepsy, and it was suggested that an increased serum concentration of S100B might be indicative of neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high levels of S100B in the serum of the cerebrospinal fluid have been reported for schizophrenia [17,18] , major depression [19] , traumatic brain damage [20,21] , brain ischemia [22,23] , neurodegenerative disease [24,25] , and during acute episodes of bipolar disorder [26] . In addition, Calik et al [27] showed elevated S100B levels in patients with different kinds of epilepsy, and it was suggested that an increased serum concentration of S100B might be indicative of neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…S100 combines with receptors for advanced glycation end-product (RAGE) in the extracellular matrix and plays a critical role in the glial modulation of neuronal synaptic plasticity 6 . The serum levels of S100-B are increased in children with temporal lobe epilepsy 7 . High RAGE expression is observed in inflammatory lesions, and the blocking of RAGE delays the development of an inflammatory response 8 .…”
Section: Introductionmentioning
confidence: 94%
“…3,15 S-100B protein levels have been suggested to be reflective of certain pathological conditions in the brain and/or bloodbrain barrier, may correlate with the overall degree of damage and be of value in predicting the extent of the damage. 16 Studies have reported elevated serum and CSF S-100B levels in patients with traumatic brain damage, 17,18 stroke, 19 subarachnoid hemorrhage, 20 schizophrenia, 21 and bacterial meningitis, [22][23][24] premature babies with hypoxic-ischemic encephalopathy and intraventricular hemorrhage, 25 and patients with temporal lobe epilepsy 26,27 compared with control subjects. Portela et al 28 reported normal S-100B protein levels in patients with focal epilepsy.…”
Section: Discussionmentioning
confidence: 99%